DAMPAK PANDEMI COVID-19 TERHADAP REALITAS MASYARAKAT PONTIANAK SERTA KAITANNYA DENGAN NILAI-NILAI AL-QUR’AN - Nadia Rahmattika (IAT IAIN Pontianak, 2023)
Life during the Covid-19 pandemic gave birth to new habits, from that habit arising values due to the fruits of public awareness in taking action in response to the spread of the Covid-19 virus which has increased several times in Pontianak City, habits that arise during the pandemic often become a burden for some of the lower middle class in Pontianak City, but not a few people are also able to take wisdom and lessons from the rampant spread of This Covid-19. The impact caused by Covid-19 also affects several sectors in Pontianak such as the economic sector, education ocial sector of society . Thus, even though the Covid-19 outbreak is considered a cruel and deadly virus and brings various unwanted adverse effects, if you look at the glasses of the Qur'an, we will find a point or value that makes the heart calmer in responding to the plague because the Qur'an is believed to be able to become a medicine or shifa' from all kinds of diseases that exist in the world because if connected the Qur'an will fully explore how to deal with Covid-19 with pay attention to the values of patience, health, and justice in the midst of a pandemic.